2021
DOI: 10.1590/s1678-9946202163030
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial treatment of Erysipelatoclostridium ramosum invasive infections: a systematic review

Abstract: The aim of this systematic review was to determine the causal role of Erysipelatoclostridium ramosum in specific invasive infections in humans, and to assess the clinical outcome of antibiotic therapy used to treat them. Several electronic databases were systematically searched for clinical trials, observational studies or individual cases on patients of any age and gender with a systemic inflammatory response syndrome (SIRS) due to E. ramosum isolated from body fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…In our study, we found that the abundance of Pseudoflavonifractor, a type 2 diabetes-related flora, was decreased in MT cattle, indicating that MSTN can regulate metabolism by regulating intestinal flora. Some flora associated with intestinal inflammation was increased in MT cattle, such as Erysipelatoclostridium [44], Prevotellaceae_Ga6A1_group [45], and Candidatus_Saccharimonas [46], whereas some flora associated with intestinal inflammation was decreased in MT cattle, such as Paraclostridium, Porphyromonas, Terrisporobacter, and Paeniclostridium. Therefore, in this study, the effect of MSTN mutation on intestinal inflammation could not be determined.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, we found that the abundance of Pseudoflavonifractor, a type 2 diabetes-related flora, was decreased in MT cattle, indicating that MSTN can regulate metabolism by regulating intestinal flora. Some flora associated with intestinal inflammation was increased in MT cattle, such as Erysipelatoclostridium [44], Prevotellaceae_Ga6A1_group [45], and Candidatus_Saccharimonas [46], whereas some flora associated with intestinal inflammation was decreased in MT cattle, such as Paraclostridium, Porphyromonas, Terrisporobacter, and Paeniclostridium. Therefore, in this study, the effect of MSTN mutation on intestinal inflammation could not be determined.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, some ARGs are directly distributed in pathogenic bacteria, such as Clostridium and Chlamydia , which can cause a variety of diseases, and Escherichia and Erysipelatoclostridium , which are common in severe infections. 53 Once the infection is rampant, it places a great burden on the host, and is difficult to treat due to the protective effects of ARGs. During clinical treatment, bacteremia patients infected with carbapenem-resistant Enterobacter-iaceae or carbapenem-resistant Pseudomonas aeruginosa suffer 40–70% mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In the AG hall (in red), the biomarker microorganism is Rhizobiales, while in the RG hall (in green), the biomarker microorganisms are Erysipelatoclostridium and Lachnospiraceae . E. ramosum , a species in the genus Erysipelatoclostridium , is a normal member of the human gut microbiota and only causes invasive infections in rare cases 27 . The members of Lachnospiraceae are the core taxa of the intestinal tract and have a high species abundance and relative abundance in the life cycle of the host.…”
Section: Results and Analysismentioning
confidence: 99%